The journey from paediatric intensive care to children's hospice. Issue 2 (1st September 2011) - Harrop, Emily; Gupta, Neelam; Lapwood, Susie; Shefler, Alison
Abstract : Introduction: Approximately 2/3 of PICU patients who die, do so as a result of withdrawal of treatment, most of these deaths occur on PICU. We have set out to examine referrals from PICU at the John Radcliffe Hospital, to Children's Hospices over a 5-year period. Aims: ▶ Investigate year-wise trend in PICU referrals to Hospices ▶ Examine the outcomes ▶ Examine the process of transfer to non-hospital settings ▶ Inform practice. Methods: Retrospective review of case notes for all children referred from a large tertiary level UK PICU to Children's Hospices over a 5-year period. Information was collected both from PICU and from the two hospices involved. Results: A total of 12 children were transferred, with referrals increasing over time. 2/3 of the children were aged 2–8 years, and the mean stay on PICU prior to transfer was 13 days. The average time from initial referral to transfer was 4 days. Discussions about limitation of treatment occurred after an average of 9 days of ventilation, with 2/3 of families having had prior contact with the palliative care team involved. 1/3 the patients were still on invasive ventilation at the time of transfer, and all of those were escorted by a PICU Consultant, of these, ¾ were extubated within 30 min of arrival at the hospice. Overall, eight children died following transfer, but four children (1/3) survived for > 2 weeks. Conclusion: It was pleasing to confirm an increase in joint working between PICU and Children's Hospices. Consistent with other studies, we have shown that 1/3 of children transferred for end of life care, initially survive. Information gained from reviewing these cases contributed to setting up a working party to produce a care pathway to support extubation within a children's palliative care framework, which is due to be published this year.